Cenoura feliz e suas propriedades - Chicaroli, Angela Maria de Oliveira; Lopes , Cleuza Francisca da Silva; Lima , Maria dos Santos; Oliveira , Maria Auxiliadora de; Guimarães , Renata Maria de Souza; Simião, Regina Aparecida Versoza; Sanches , Silvane Souza Meneses (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf